A107 DISEASE DISTRIBUTION AND CLINICAL FEATURES OF INFLAMMATORY BOWEL DISEASE IN PATIENTS WITH PRIMARY SCLEROSING CHOLANGITIS: A SINGLE-CENTRE RETROSPECTIVE ANALYSIS. (15th March 2019) - Donaldson, K; Enns, R A; Bressler, B; Ko, H
Abstract: Background: Inflammatory bowel disease (IBD) associated with primary sclerosing cholangitis (PSC) has previously been reported to have different clinical characteristics compared to IBD without PSC. Aims: The aim of this study was to describe the pattern of intestinal disease distribution and clinical features of PSC-IBD at a Canadian tertiary care centre. Methods: A retrospective chart review was conducted on all PSC-IBD patients followed at the PSC clinic at a tertiary care centre in Vancouver, Canada, between January 2010 and June 2018. Data collected and analyzed included demographics, medical history, biochemical and imaging results, operative records, and pathology reports. For patients with PSC-ulcerative colitis (UC), disease severity was graded using the Endoscopic Mayo Score. Distal vs. proximal colonic segments were defined relative to the splenic flexure. Results: 69 PSC-IBD patients were identified, 44 (63.8%) were male. Mean age of IBD diagnosis was 28.6 (SD 14.9) years, and PSC was 37.0 (SD 18.9) years. PSC diagnosis preceded IBD in 3 (4.3%) patients. Median length of follow up was 12 (range 2–49) years. Of the PSC-IBD patients, 52 (75.4%) had UC. Among PSC-UC patients, on initial endoscopic assessment, 87.5% had pancolitis, and 12.5 % had proctitis. Among PSC-UC patients with pancolitis, 28.6% had relative rectal sparing (rectal mucosa was either endoscopically normal, or much less inflamed than sigmoid). Of the PSC-UC patients with pancolitis, 14.3% had more severe inflammation in proximal vs. distal colon, whereas only 3.6% had more severe inflammation in distal colon. The remaining 82.1% had the same degree of inflammation throughout. For all PSC-UC patients, no granulomas were found on histology. All patients with PSC-Crohns disease (CD) had colonic involvement on endoscopic exam at diagnosis. Of the PSC-IBD patients, 16 (23.2%) had colectomy. Excluding those with colectomy, 40 (75.5%) patients were on IBD treatment at the time of data extraction. In this PSC-IBD population, 8 (11.6%) patients had cholangiocarcinoma, 1 (1.4%) had colorectal cancer, and 1 (1.4%) had gallbladder cancer. Conclusions: In this PSC-IBD cohort, pancolits was common, with more severe inflammation in the proximal colon, and frequent rectal sparing. This pattern of disease distribution is in concordance with previous population-based studies performed outside of Canada. While rates of colorectal and gallbladder cancer in this cohort were low, cholangiocarcinoma developed in a substantial fraction of patients. These findings support that IBD with PSC may represent a distinct IBD phenotype. Awareness of these distinctive patterns is important in directing appropriate investigations, surveillance, and treatment for these patients. Funding Agencies: None